Diseño e Implementación de una estación meteorológica móvil para la obtención de datos medioambientales en escenarios controlados en la Provincia de Chimborazo - Garcés Palacios, Luis Enrique (2019)
Nowadays, climate change and its effects directly or indirectly affect human activities and the lives of living beings in general. As a result of the increase in temperatures and especially greenhouse effect gases, is being provoked, among other problems, the melting of the polar caps and the gradual increase of the sea level. Likewise, in Ecuador, the immediate effect of climate change has been the retreat of the main snow-capped mountains and specifically Chimborazo, located in the province with the same name. Consequently, the collection of environmental data such as temperature, humidity, pressure, altitude, CO2 (carbon dioxide) level, TVOC (TOTAL VOLATILE ORGANIC COMPOUNDS) and UV radiation are vital importance for the study, mitigation and prevention of natural disasters. This project shows the implementation of a mobile meteorological station prototype, designed for the monitoring, measurement and analysis of physical environmental variables in controlled scenarios in the province of Chimborazo. Additionally, the values collected will be compared in the database that National Institute of Meteorology and Hydrology holds in order to validate the operation of the prototype